1983
DOI: 10.1007/bf00289473
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of chromosomal genotypes associated with Turner's syndrome: livebirth prevalence rates and evidence for diminished fetal mortality and severity in genotypes associated with structural X abnormalities or mosaicism

Abstract: The proportions of chromosomal genotypes associated with the Turner syndrome genotype (excluding those with a Y chromosome) in embryonic and fetal deaths, in fetuses diagnosed prenatally, and in living individuals were reviewed. The ratio of apparent non-mosaic 45,X to 45,X/46,XX mosaics was notably higher in a New York City series of embryonic and fetal deaths, 13.5 to 1, than in living individuals reported to the New York State Chromosome Registry, 3.6 to 1. The ratios of 45,X cases to those with 46,Xi(Xq) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
202
2
12

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(220 citation statements)
references
References 9 publications
4
202
2
12
Order By: Relevance
“…Turner syndrome individuals frequently show mosaicism (Hook and Warbuton, 1983;Robinson, 1990) and the presence of a normal cell lineage along with the 45,X lineage is considered to increase the probability of survival of those with 45,X Turner syndrome (Held et al, 1992, Kelly et al, 1992.…”
mentioning
confidence: 99%
“…Turner syndrome individuals frequently show mosaicism (Hook and Warbuton, 1983;Robinson, 1990) and the presence of a normal cell lineage along with the 45,X lineage is considered to increase the probability of survival of those with 45,X Turner syndrome (Held et al, 1992, Kelly et al, 1992.…”
mentioning
confidence: 99%
“…A incidência da ST é estimada em torno de 0,47 por 1.000 ou 1 em cada 2.130 nativivas (38). O número de recém-nascidas corresponde, porém, a uma pequena fração do total de conceptos com ST, uma vez que, embora 1 a 2% de todas as concepções humanas tenha a constituição cromossômica 45,X, cerca de 99% dos conceptos 45,X são abortados espontaneamente (39).…”
Section: Síndrome De Turnerunclassified
“…Approximately half of the unidentifiable marker chromosomes that have an estimated frequency of 3% are Y-derived [6,7]. It has been speculated that most Turner syndrome patients with putative non mosaic 45,X karyotype have an undetected mosaicism, based on an analysis which revealed that less than 1% of 45,X conceptions survive pregnancy [8]. Several investigators have postulated that in 45,X patients, fetal survival needs SRY GENE IN TURNER SYNDROME mosaicism in at least some organ or tissue [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that most Turner syndrome patients with putative non mosaic 45,X karyotype have an undetected mosaicism, based on an analysis which revealed that less than 1% of 45,X conceptions survive pregnancy [8]. Several investigators have postulated that in 45,X patients, fetal survival needs SRY GENE IN TURNER SYNDROME mosaicism in at least some organ or tissue [8,9]. Patients with the SRY gene require special attention since the presence of a Y chromosome correlates with a 10-20% risk of developing gonadoblastoma or dys germinoma later in life [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation